(3OQGSI ebGQfI Hjf GdENJHGQ (B( T) (3hGdENJHGQ GdebJQM (B( Y ) (3GdejOGfjjf dbjGS UaJj GdSQYI hGdQTGbI (B: (3OQGSI JLQjHjI CLQjJ Ydi WdHI eYgO Ydhe hJbfjGJ GdfTGWGJ GdHOfjI hGdQjGVjI HJSeSjdJ s - (3MhGaj , ajUds; (3HhQfGf, eUWai TQjas; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3YJHQ GdEfLGR GdQjGVj GdgOa GdefThO dOi LejY GdQjGVjf aj GdejGOjf hGdJNUUGJ GdQjGVjI GdeJfhYI, gfG bGe GdbGFejf Ydi GdYedjI GdJOQjHjI hGdeNJUjf Ydi JNUjU bOQ cHjQ ef GdYed GdODhH hGdLGO aj YedjI GdHMK Yf CMOK hSGFd bjGS hdENJHGQ ddfTGWGJ GdHOfjI GdQjGVjI hCaVd GdhSGFd GdefGSHI hGdMOjKI, hgOaJ OQGSJfG gPg Edi EbJQGMENJHGQ ejOGfj HOfj dbjGS GdUaJjf GdHOfjJjf GdSQYI hGdQTGbI, dOi YjfI eJfhYI GdCaQGO JeKdJ aj WdHI eYgO Ydhe hJbfjGJ GdfTGWGJ GdHOfjI hGdQjGVjI HLGeYI JjSeSjdJ, eHfj Ydi GdCSS GdYdejI GdUMjMI (B( (3UOb KHGJ hehVhYjI(B)(3, hehGab deQGMd hTQhW EbJQGMGdENJHGQGJ GdejOGfjI GdHOfjI, hhVY LOGhd eYjGQjI TedJ eJZjQ GdLfS (B((3PchQ hEfGK(B)(3, heJZjQ GdeeGQSI GdQjGVj (B( (3eeGQS ZjQ eeGQS(B)(3, eY eQGYGJ LejY GdaQhb hYdi gPG GdCSGS befG HEaJQGV Cf GdENJHGQ GdejOGfj GdebJQM jJeJY HeSJhi YGd ef GdehKhbjI hGdUdGMjI hgPG NSHeGbGeJ GdeYGedGJ GdEMUGFjI HEKHGJg hGdeUGObI Ydjg, hab GdefgL GdJLQjHj HMjK JeKdJ YjfI GdHMK aj (B(365 (3WGdH(B)(3, ef eNJda GdeSJhjGJ Je GdbjGe HENJjGQge HGdWQjbI GdYThGFjI, hdYedjI JMUjd GdfJGFL hLeY GdHjGfGJ beJ HESJNOGe COGI JeKdJ aj ENJHGQ ejOGfj HOfj ebJQM, hHYO GdbjGe HLeY GdHjGfGJ ef GdejOGf hJaQjZgG heYGdLJgG EMUGFjG hJMOjO GdLOGhd GdeYjGQjI Je GdhUhd deMehYI ef GdfJGFL ef Hjf CgegG Cf GdENJHGQ GdejOGfj GdebJQM dbjGS GdUaJjf GdHOfjJjf (B((3GdSQYI hGdQTGbI(B)(3, jJejR HeSJhi YGd ef GdKHGJ hGdUOb hGdehVhYjI hYdjg jecf GdhKhb HfJGFLg aj YedjI GdbjGS ebGQfI HfJGFL GdENJHGQ GdeMcj GdPj JejRJ fJGFLg HGdKHGJ hGdUOb HeYGedGJ YGdjI LOG(B.s
(3OcJhQGIs
Keywords: (3GdJOQjH GdQjGVjs; (3GdQTGbIs; (3GdSQYIs; (3GdUaGJ GdHOfjIs